The worldwide coronavirus disease 2019 outbreak: Advice and recommendation on radiology management and infection control from makeshift hospitals in Wuhan. Issue 19 (14th May 2021) - Mu, Lin; Zhang, Caijuan; Pei, Yun; Wang, Jingyu
Abstract : Abstract: To describe and advise on management protocols and infection-protection experience of the radiology department in makeshift hospitals in Wuhan during the coronavirus disease 2019 (COVID-19) outbreak. Based on the literature review and the experience in the frontline, we retrospectively reviewed the configuration of the radiology department, human resource, personal protection, examination procedures for patients confirmed with COVID-19 in Wuhan fangcang shelter hospital. From February 11, 2020 to March 10, 2020, 2730 and 510 CT examinations were performed in the Hanjiang shelter hospital and Hanyang Sports School shelter hospital, respectively, including initial examinations and re-examinations. The maximum number of daily CT examinations reached 289. The CT scanned a patient approximately once every 13 mins. Fangcang shelter radiology department could be powerful components of both global and national responses to the COVID-19 pandemic.